2020
DOI: 10.1016/j.tra.2019.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the adoption and use of urban air mobility

Abstract: Technological advances have recently led to the development of urban air mobility (UAM), an alternative transportation mode with several concepts including vehicles operated by on-demand fully-automated vertical take-o↵ and landing aircraft (VTOL) for intra-city passenger transportation. However, despite a growing interest in UAM, understanding users' perceptions to it remains limited. This research aims to identify and quantify the factors a↵ecting the adoption and use of UAM, based on relevant tools from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 45 publications
8
96
0
1
Order By: Relevance
“…User adoption : With regard to user acceptance, Al Haddad et al [ 34 ] have conducted an empirical study on which factors the willingness to use UAM depends on. In respect to existing research they confirmed the influence of the user sense of security towards UAM and the perceived trustworthiness of the service provider.…”
Section: Basis For Passenger Urban Air Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…User adoption : With regard to user acceptance, Al Haddad et al [ 34 ] have conducted an empirical study on which factors the willingness to use UAM depends on. In respect to existing research they confirmed the influence of the user sense of security towards UAM and the perceived trustworthiness of the service provider.…”
Section: Basis For Passenger Urban Air Mobilitymentioning
confidence: 99%
“…Further decision factors are the expected reduction of the individuals travel time, the estimated reliability of the offered service and the user perception of automation costs. Also shown to be relevant were the potential user attitude towards automation, data security as well as demographic characteristics of the respondents [ 34 ]. Studies further stress on the importance of the availability (e.g., in the form of on-demand services), the costs and the accessibility of the service (e.g., the distribution and accessibility of vertiports).…”
Section: Basis For Passenger Urban Air Mobilitymentioning
confidence: 99%
“…The goal is to support mobility users sustainably through intelligent route planning, booking, travel and flight as well as payment processes. Social acceptance is a key success factor for the comprehensive use of UAM [20]. This is primarily achieved through seamless and safe processes.…”
Section: Operational and Business Models Conceptsmentioning
confidence: 99%
“…With this prototype showing a strong connection between the commercial core of Chicago, policies should focus on connections that will appeal to business travelers. This remains a challenging area of research, as new options, including vertical urban air mobility, are being tested in initiatives such as UberElevate with electric vertical takeoff and landing vehicles ( 41 , 42 ). This highlights the need to craft regulations and partnership arrangements such as security checkpoints and luggage drop-offs ( 43 ).…”
Section: Policy Implicationsmentioning
confidence: 99%